2011
DOI: 10.1002/cbdv.201000102
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Volatile Leaf Oils of Five Eucalyptus Species Harvested from Jbel Abderrahman Arboreta (Tunisia)

Abstract: Hydrodistillation of the dried leaves of five species of the genus Eucalyptus L' Hér., viz., E. dundasii Maiden, E. globulus Labill., E. kitsoniana Maiden, E. leucoxylon F. Muell., and E. populifolia Hook., harvested from Jbel Abderrahman arboreta (region of Nabeul, northeast of Tunisia) in April 2006, afforded essential oils in yields varying from 0.9±0.3 to 3.8±0.6%, dependent on the species. E. globulus and E. Kitsoniana provided the highest and the lowest percentage of essential oil amongst the species exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The chromatographic analysis (GC retention index (RI) and GC/MS) of the essential oils allowed the identification of 144 components representing 87.40 to 99.37% of the total oil content [23-25]. Twenty five major compounds at an average concentration greater than 0.9 ± 0,2% have been retained for the statistical analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The chromatographic analysis (GC retention index (RI) and GC/MS) of the essential oils allowed the identification of 144 components representing 87.40 to 99.37% of the total oil content [23-25]. Twenty five major compounds at an average concentration greater than 0.9 ± 0,2% have been retained for the statistical analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…-In our previous studies published on Eucalyptus species growing in Tunisia, we have characterized the leaf essential oils of 19 Eucalyptus species harvested from Hajeb Layoun arboreta (center of Tunisia) [1] [2], 13 species from Souinet arboreta (north of Tunisia) [3], 11 species from Korbous arboreta (northeast of Tunisia) [4], and 5 from Jbel Abderrahman arboreta (region of Nabeul, northeast of Tunisia) [5]. Continuing our investigations on Tunisian Eucalyptus species, we report here the results of our research on the variability of eight leaf essential oils from seven Eucalyptus species, viz., E. cladocalyx F.…”
mentioning
confidence: 99%
“…Unlike most of the other rare species considered here, two references indicate the ability of E. kitsoniana to grow under warmer conditions than those within its natural distribution. For example, Elaissi et al (2011) reported on leaf oils from E. kitsoniana grown at Jbel Abderrahman Arboretum near Nabuel (36.4561 o N, 10.7376 o E) in Tunisia where the annual mean temperature is 17.9 o C and the annual mean precipitation is 358 mm. Siddiqui et al (1985) discuss the suitability of E. kitsoniana for growing in Pakistan after the species produced "very good growth and acceptable survival" at Mirpur Mathelo ( .…”
Section: E Kitsoniana Maiden (Gippsland Mallee)mentioning
confidence: 97%